Hepatic epithelioid hemangioendothelioma of presentation as single focal incidental lesion: case report - Padilla Flores, Juan Roberto (2018)
Hepatic epithelioid hemangioendothelioma (HEH) is a very rare malignant vascular tumor of endothelial origin, of slow progression and low malignity degree. It is more common in women, of unknown etiology. Clinical manifestations of HEH are non-specific, from asymptomatic to abdominal pain. The more frequent radiological features are nodular hepatic lesions, of variable size, which show appearance of "target sign" in computed tomography (CT) and magnetic resonance imaging (MRI), with capsular retraction. Hepatic metastases are the principal differential diagnosis. The clinical course is variable, with a mortality rate to the diagnosis of up to 50 % of the patients. The therapeutical options include the surgical extirpation (removal) of the tumor and hepatic transplant as the more useful, besides the regional /systemic chemotherapy and immunological treatment. The present case describes the principal clinical - pathological characteristics of this rare tumor, with the particularity of its form of presentation as focal lesion, besides the therapeutical modality used (surgical removal) in this type of illness.